Lowering the target daily light integrals following days with excessive lighting can reduce lettuce production costs - Andres M. Mayorga-Gomez; Marc W. van Iersel; Rhuanito Soranz Ferrarezi (Frontiers in Plant Science)
Given the fluctuating availability of natural lighting throughout the year, supplemental light is frequently employed to maintain the optimal daily light integral (DLI) levels necessary for adequate plant growth. However, the use of supplemental light translates into higher operational costs. Recent reports suggest that plants can tolerate a day with low DLI following exposure to a day with high DLI from natural light. This was referred to as the ‘carryover’ effect. In such cases, supplemental lighting may not be necessary, resulting in energy savings. In this study, we determined if plants can withstand such DLI fluctuations over multiple days without compromising plant growth. Additionally, we calculated the energy requirements for trese treatments to evaluate the potential energy savings of the carryover effect. To test this, we cultivated lettuce plants (Lactuca sativa cv. ‘Waldmand’s Dark Green’ and ‘Rouxai’) in a walk-in grow chamber, subjecting them to six different lighting treatments. Each treatment consisted of a day with a high DLI of 22.5 mol·m-2·d-1 followed by a varying number of consecutive days with low DLI, ranging from 1 to 5 days, with DLIs of 7.5, 11.25, 12.5, 13.13, and 13.5 mol·m-2·d-1 respectively. The combined DLI for each treatment, calculated as the average DLI across high and low DLI days, was maintained at 15 mol·m-2·d-1. Additionally, we included a control treatment where plants were exposed to a constant DLI of 15 mol·m-2·d-1. We measured plant growth rate, final fresh and dry weights, leaf number, leaf area, specific leaf area, light use efficiency, and relative pigment content to assess differences in plant growth under the different lighting regimes. We observed a decrease in biomass accumulation, as indicated by a 13% reduction in final dry weight only for the treatment involving one day of high DLI followed by one day of low DLI, compared to our control. We discovered that plants can tolerate multiple days of low DLI following a day with high DLI, in contrast to the optimal values reported in the literature. This finding can lead to reduced energy consumption for supplemental lighting and consequent operational cost savings.